Cultivating focus: insights from dedicated yoga practice and the implications for mental health and well-being. Issue 2 (14th March 2016) - Halsall, Tanya; Werthner, Penny; Forneris, Tanya
Abstract: Yoga has demonstrated some promising impacts on mental health and well-being. The ability to focus is a possible mechanism through which yoga practice influences mental health and well-being. Furthermore, there are relatively few empirical studies that have explored the experience of maintaining focus or the process of developing this capacity within yoga. This study explored focus in terms of its development within the practice of yoga. The two objectives of the study were: (1) to examine the experience of focus in individuals with extensive accumulated practice, and (2) to learn how they developed this ability to focus. Eight participants were selected based on duration and frequency of their practice. Two one-hour interviews were conducted with each participant in a semi-structured format and qualitative thematic analysis was used. The findings are discussed within two main themes: the practice and the nature of yogic awareness. Results are discussed in relation to the enhancement of mental health and well-being, and future directions are recommended.